Lipid-lowering effect and oral transport characteristics study of curculigoside - Wang, Aiping; Ning, Jie; Zhao, Lu; Xu, Renjie (Frontiers in Cardiovascular Medicine, 2024)
The incidence of metabolic disorders during pregnancy is increasing year by year, with diseases including hypertension and hyperlipidemia. Statins are the primary drugs for treating hyperlipidemia or atherosclerosis, yet some patients remain unresponsive to them, and pregnant women are prohibited from taking statins. Curculigoside is the major biologically active natural product present in Curculigo orchioides. In this study, A high-fat mice model was developed to study the lipid-lowering effect of curculigoside. Using intestinal Caco-2 cell monolayer, the curculigoside transport properties at two temperatures and possible transporters were systemically studied. Curculigoside at concentrations used during the experiments have no toxic effect to Caco-2 cells. The curculigoside transfer from the apical to the basolateral side was strongly influenced by temperature. P-glycoprotein, breast cancer resistance protein, and efflux transporters are crucial components of the human intestinal cell line Caco-2. The curculigoside can significantly affect the contents of total cholesterol, triglycerides, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol in mice. The transport properties and potential mechanism of curculigoside offer valuable insights for the design of development of hypolipidemic drugs like anti-atherosclerotic drugs and also be helpful to the further study of the pharmacological activity of curculigoside.